P‐6.9: Big Data and Cloud Service—A Mask Intelligent Handling System. (28th November 2018) - Zou, Zehua; Pan, Jiangshen; Xin, Xiandong; Yang, Jia; Chen, Xiaochun; Jiang, Yunkang; Zhang, Xijian
Abstract : With the popularization of information and automation, an automatic handling system has been gradually applied to various industries of intelligent manufacturing. For the intelligent management of Mask in TFT‐LCD industry, unmanned transport has naturally become a key tool for factories to enhance competitiveness and expand profitability. Meanwhile, the Mask cost exponentially increases with the increasing generation lines. In order to create leading global G10.5 production line, a Mask intelligent handling system including MES, ACS and AGV is built. As the system brain, MES is responsible for collecting production information and processing big data. ACS can collect Mask information, accept MES instruction and coordinate the logical actions among different devices. AGV acts as an implementer to carry out the specific implementation of Mask movement. The Mask intelligent handling system has been implemented at present, and it plays an important role in the improvement of the business productivity and corporate profits.